Real and nominal wage rigidities in collective bargaining agreements - Louis N. Christofides; Paris Nearchou (Institute for the Study of Labor (IZA), 2007)
An earlier study of wage agreements, reached in the Canadian unionized sector between 1976-99, found that wage adjustment is characterized by downward nominal rigidity and significant spikes at zero. We extend this earlier approach to encompass the possibility of real as well as nominal wage rigidity. The addition of real wage rigidity variables enhances earlier results and suggests that real rigidity increases significantly the mass in the histogram bin containing the mean anticipated rate of inflation, as well as in adjacent bins. Downward nominal wage rigidities and spikes at zero remain important.
urn:nbn:de:101:1-20080401318
Keywords: 330; Lohnrigidität; Lohnverhandlungstheorie; Inflation; Kanada